Tensile Strength of Bamboo After Preservation - Noverma; Hapsari, Oktavi Elok; Yusrianti (Proceeding International Conference on Science and Engineering, 2020)
Bamboo has high tensile strength, so it can be an alternative to substitute wood or steel. Bamboo is a material that comes from nature, so it is vulnerable to degraded by weather changes and infected by termites and fungi. The effort to overcome this problem is by preserving before using it. This study aims to determine the tensile strength test results of bamboo after preserving and then compare with the tensile strength test results of bamboo without preserving. The research method was carried out by preserving bamboo by soaking the test sample in a container filled with water for a duration of time; 1 x 24 hours; 3 x 24 hours and 14 x 24 hours. The water used in freshwater with a salinity of 0 0/00 measured using a salinometer. The results showed that the tensile strength of bamboo increased compared without preserved with a percentage of 12.50%; 23.12% and 10.59% for the duration of time respectively 1x24 hours; 3x24 hours and 14x24 hours. Optimal tensile strength is obtained at a time duration of 3 x 24 hours and decreases at a longer time duration of 14x24 hours.